Females Exhibit Greater Peak and Cumulative Patellofemoral Joint Stress With Moderate and Heavy Load Carriage Compared With Males - Willy, Richard W.; Simon, Janet E.; Hanser, Brittany; Plemmons, Marin; Christensen, Kelly; Klawitter, Lexi; Doutt, Alexis; Ruby, Brent C. (European journal of sport science, 2025)
Load carriage training is universal during military training, regardless of sex or physical characteristics, and may contribute to the 1.3‐2.2× higher incidence of patellofemoral pain (PFP) in female versus male recruits. This study aimed to assess sex differences in patellofemoral joint (PFJ) stress during load carriage, controlling for anthropometrics and quadriceps strength. Twenty males and 20 females walked (1.35 m/s) on an instrumented treadmill with 0‐kg, 20.4‐kg, and 34.0‐kg of load carriage. An inverse‐dynamics musculoskeletal model estimated peak, impulse, and cumulative PFJ stress. To assess quadriceps strength, peak isometric knee extensor torque normalized to body mass was measured via dynamometry. Analyses of covariance (ANCOVA) adjusting for body mass, height, and quadriceps strength assessed the effects of load (0‐kg, 20.4‐kg, and 34.0‐kg) and biological sex (male, female) on PFJ stress and gait parameters. Females were shorter, had lower mass, and lower quadriceps strength (all p <  0.001; d =  1.50–1.54, indicating large effect sizes). Peak, impulse per step, and cumulative PFJ stress increased with load carriage, with greater increases in females compared to males (sex × load interactions p =  0.002–0.005; η p 2   =  0.12–0.13, indicating moderate effect sizes) after controlling for body mass, height, and quadriceps strength. These data indicate that anthropometrics and quadriceps strength do not explain the substantially greater increases in per step and cumulative PFJ stress in females versus males with load carriage. Female recruits may benefit from targeted prevention efforts, such as slower progressions of load carriage training, either in amount carried or distance trained, to reduce their risk of PFP. Females were shorter, with lower body mass, and lower absolute‐ and body‐mass normalized‐isometric quadriceps strength. Disproportionately greater increases in patellofemoral joint stress were observed in females compared with males when walking with moderate (20.4‐kg) and heavy (34.0‐kg) load carriage, while controlling for height, body mass, and isometric quadriceps strength. When walking with the load carriage, shorter step length, shorter stance time, and increased trunk flexion were observed in females compared to males. However, these sex differences were no longer present after adjusting for height, body mass, and isometric quadriceps strength in the analysis.